Depreciation, inflation and capital replacement* - MOORE, GIORA (Contemporary Accounting Research, 1987)
Abstract. This paper examines the effects of depreciation, taxes and inflation on the optimal timing of asset replacement in accordance with the Canadian tax laws. The main findings are that an increase in the capital cost allowance rate will delay (accelerate) replacement of fixed assets at low (high) levels of capital cost allowance rates, and that an increase in the annual inflation rate will delay (accelerate) replacement of fixed assets at low (high) levels of inflation. The applications of the replacement model are illustrated with numerical examples.